IDENTIFICATION OF HOLSTEIN COWS CARRIERS OF COMPLEX VERTEBRAL MALFORMATION BY HIGH RESOLUTION MELTING CURVES (HRM) - Branda Sica, Andrea; Nicolini, Paula; Federici, María Teresa; Llambí, Silvia (Archives of Veterinary Science, 2019)
The objective of this study was the optimization and implementation of a reliable and economical molecular screening method for the detection of the mutant allele of CVM (complex vertebral malformation, c.559G>T, SLC35A3) by HRM analysis, as well as analyzing its existence in a representative sample of Holstein cows from the Milk Genomic DNA Bank of Uruguay. The optimization of the HRM methodology in the RotorGene™ 6000 equipment (Corbett Life Science, Australia) by amplification of the 79 bp PCR products clearly differentiated the two genotypes: homozygous, wild type: GG; and heterozygous, carrier for the mutation CVM: GT (c.559G>T; SLC35A3). In the analyzed sample, the frequency of the mutant allele (T) for CVM was high (q = 0.032), with a prevalence of carrier cows of 6.45%. It is concluded that the PCR-HRM analysis is a fast, easily interpretable, low cost, and highly accurate technique for the detection of this mutation in Holstein cattle, which may be implemented in genetic selection programs.